Coronavirus Disease 2019 Serial Testing Among Hospitalized Patients in a Midwest Tertiary Medical Center, July–September 2020. (29th October 2020) - Kobayashi, Takaaki; Trannel, Alexandra; Holley, Stephanie A; Alsuhaibani, Mohammed A; Abosi, Oluchi J; Jenn, Kyle E; Meacham, Holly; Sheeler, Lorinda L; Etienne, William; Dains, Angelique; Casado, Fernando; Kukla, Mary E; et al.
Abstract: We implemented serial coronavirus disease 2019 testing for inpatients with a negative test on admission. The conversion rate (negative to positive) on repeat testing was 1%. We identified patients during their incubation period and hospital-onset cases, rapidly isolated them, and potentially reduced exposures. Serial testing and infectiousness determination were resource intensive.